Perbandingan Hak dan Kewajiban dalam Kontrak Konstruksi yang Berlaku dengan Standar FIDIC Pada Proyek Konstruksi di Kabupaten Manokwari: Comparison Of Rights and Obligations in Applicable Construction Contracts with Fidic Standards on Construction Projects in Manokwari District - Nur Azizah Syarif; Indra Birawaputra (JISTECH: Journal of Information Science and Technology, 2025)
Nur Azizah Syarif, Department of Civil Engineering, Bachelor of Civil Engineering Study Program, University of Papua, Starting February 2024 started this research which aims to find out the rights and obligations regulated in construction work contracts on construction projects in Manokwari Regency, the rights and obligations regulated in FIDIC documents related to construction work contracts and find out the advantages and disadvantages of using FIDIC document standards and SSUK. The FIDIC document standard used as a reference is the FIDIC Red Book 2017 and SSUK Unit Price. In this research, the author the method used in this research is descriptive and qualitative, namely a research method that seeks to describe and interpret what exists. Data analysis or interpretation is the process of systematically searching and organizing records of research findings through observation and others which are useful for increasing the researcher's understanding of the focus being studied and making it a finding for others, editing, clarifying, reducing, and presenting it. Meanwhile, qualitative data analysis is carried out by categorizing and analyzing answers based on themes or patterns that emerge from interviews and using qualitative analysis techniques to interpret data and draw conclusions.